ESG Score and Sharia Compliance as Determinants of Foreign Investment Flows into Sharia Stocks: A Multinational Panel Analysis 2019-2024 - Mastiah; Muhamad Arifin; Khalifa Damalin Ayunda (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study analyzes the influence of ESG Score and sharia compliance on Foreign Portfolio Investment (FPI) in Indonesia and Malaysia during the 2019–2024 period. Using a panel data approach on the JII and FBMHS indices, the results indicate that ESG Score has a significant positive effect on FPI, highlighting the growing importance of sustainability performance for global investors. Sharia compliance, represented by the Debt-to-Asset Ratio (DAR) and Islamic Income Ratio (IIR), also significantly affects FPI, suggesting that adherence to Islamic financial principles strengthens foreign investor confidence in Islamic capital markets. Simultaneously, the integration of ESG performance and sharia principles emerges as an important determinant of cross-border investment decisions. However, this study operationalizes sharia compliance using limited financial ratio proxies, which may not fully capture the multidimensional characteristics of Islamic screening standards. Broader aspects such as business activity screening, non-halal income purification, and Islamic governance mechanisms were not included in the analysis. Therefore, future studies are encouraged to incorporate more comprehensive qualitative and governance-related indicators of sharia compliance to better explain foreign investor behavior in Islamic capital markets. These findings provide strategic implications for regulators and issuers to strengthen the competitiveness of Islamic capital markets through more standardized sustainability and sharia governance reporting.